REVOLUSI TEKNOLOGI DALAM PENDIDIKAN ISLAM DI ZAMAN GLOBALISASI - Putri, Neni; Yanto, Murni; Istan, Muhammad; Destriani, Destriani (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2024)
In the current era of globalization, people all over the world, including Indonesia, are feeling the big impact of technological advances. Huge advances in information technology have allowed us to quickly access a variety of content from all over the world. This relates to the study's overall objective, which is to analyze the impact of current technology on Islamic education in a globalizing world. Because of this, information is obtained through a survey of relevant scholarly literature. By using this method, the author can discover the impact of technology on education in the era of globalization. In this analysis, community culture, materialistic individuals, privatization of education, and technological dependence are considered. The education sector faces many challenges in the current era of globalization. They come from external sources. There are advantages and disadvantages to these outside issues and causes. On the other hand, this allows Islamic schools to remain true to Islamic teachings while advancing in sophistication, creativity, and innovation.